Long noncoding RNAs in triple‐negative breast cancer: A new frontier in the regulation of tumorigenesis. Issue 12 (8th June 2021) - Thakur, Krishan K.; Kumar, Aviral; Banik, Kishore; Verma, Elika; Khatoon, Elina; Harsha, Choudhary; Sethi, Gautam; Gupta, Subash C.; Kunnumakkara, Ajaikumar B.
Abstract: In recent years, triple‐negative breast cancer (TNBC) has emerged as the most aggressive subtype of breast cancer and is usually associated with increased mortality worldwide. The severity of TNBC is primarily observed in younger women, with cases ranging from approximately 12%–24% of all breast cancer cases. The existing hormonal therapies offer limited clinical solutions in completely circumventing the TNBC, with chemoresistance and tumor recurrences being the common hurdles in the path of TNBC treatment. Accumulating evidence has correlated the dysregulation of long noncoding RNAs (lncRNAs) with increased cell proliferation, invasion, migration, tumor growth, chemoresistance, and decreased apoptosis in TNBC. Various clinical studies have revealed that aberrant expression of lncRNAs in TNBC tissues is associated with poor prognosis, lower overall survival, and disease‐free survival. Due to these specific characteristics, lncRNAs have emerged as novel diagnostic and prognostic biomarkers for TNBC treatment. However, the underlying mechanism through which lncRNAs perform their actions remains unclear, and extensive research is being carried out to reveal it. Therefore, understanding of mechanisms regulating the modulation of lncRNAs will be a substantial breakthrough in effective treatment therapies for TNBC. This review highlights the association of several lncRNAs in TNBC progression and treatment, along with their possible functions and mechanisms. Abstract : The current review mainly highlights the deregulated long noncoding RNAs associated with different hallmarks of triple‐negative breast cancer (TNBC) like proliferation, apoptosis, migration, invasion, metastasis, chemoresistance, and stemness. The focus of the manuscript is to elucidate the specific lncRNAs roles as oncogenes or tumor suppressors through extensive literature mining that might be useful for establishing these as biomarkers for diagnosis and prognosis. Through this review, we provide insights into the role of these pleiotropically acting RNA molecules at different levels of hallmarks in TNBC tumorigenesis and reflect on the chances of understanding and manipulating these candidate molecules to develop newer diagnostic and therapeutic strategies.